Assessment of drought conditions using HJ-1A/1B data: a case study of Potohar region, Pakistan. Issue 1 (1st January 2018) - Aziz, Adnan; Umar, Mudassar; Mansha, Muhammad; Khan, Mehwish Shafi; Javed, Muhammad Naveed; Gao, Hailiang; Farhan, Suhaib Bin; Iqbal, Imran; Abdullah, Shaikh
Abstract: Drought is a natural disaster which causes global damages and affects people. In this work, a comparative study of different drought indices such as Normalized Difference Vegetation Index (NDVI), Deviation NDVI (DevNDVI), Vegetation Condition Index (VCI) and Temperature Condition Index (TCI) from HJ-1A/1B multispectral data is discussed. These indices have shown potential to detect the drought severity. The objective of this study is to monitor drought in the Potohar region using HJ-1A/1B satellite data, from late November to April during 2009–2014. Additionally, results obtained from satellite data have been verified using ground-based rainfall and crop yield data. The results concluded that the Potohar region faced drought condition in 2010, which is further verified by ground data. Furthermore, NDVI and VCI in this region are found more effective than other drought indices. On the basis of validation of individual drought index with crop yield data, each index is assigned weight accordingly. Moreover, the combination of indices has the ability to detect time periods where drought is affecting the yield production. Regular monitoring and mapping of satellite-based drought indices would play an important role in predicting drought conditions.